Dual impact of elevated temperature on plant defence and bacterial virulence in Arabidopsis. Issue 1 (December 2017) - Huot, Bethany; Castroverde, Christian; Velásquez, André; Hubbard, Emily; Pulman, Jane; Yao, Jian; Childs, Kevin; Tsuda, Kenichi; Montgomery, Beronda; He, Sheng Yang
Abstract Environmental conditions profoundly affect plant disease development; however, the underlying molecular bases are not well understood. Here we show that elevated temperature significantly increases the susceptibility ofArabidopsis toPseudomonas syringae pv.tomato (Pst ) DC3000 independently of the phyB/PIF thermosensing pathway. Instead, elevated temperature promotes translocation of bacterial effector proteins into plant cells and causes a loss of ICS1-mediated salicylic acid (SA) biosynthesis. Global transcriptome analysis reveals a major temperature-sensitive node of SA signalling, impacting 60% of benzothiadiazole (BTH)-regulated genes, includingICS1 and the canonical SA marker gene, PR1 . Remarkably, BTH can effectively protectArabidopsis againstPst DC3000 infection at elevated temperature despite the lack ofICS1 andPR1 expression. Our results highlight the broad impact of a major climate condition on the enigmatic molecular interplay between temperature, SA defence and function of a central bacterial virulence system in the context of a widely studied susceptible plant–pathogen interaction. Temperature is known to influence plant disease development. Here Huot et al. show that elevated temperature can enhancePseudomonas syringae effector delivery into plant cells and suppress SA biosynthesis while also finding a temperature-sensitive branch of the SA signaling pathway inArabidopsis .